2019
DOI: 10.31616/asj.2018.0306
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Adult Spinal Deformity with Sagittal Imbalance Using Oblique Lumbar Interbody Fusion: Can We Predict How Much Lordosis Correction Is Possible?

Abstract: Study DesignProspective, single-center study.PurposeThe current trend of operative treatment for adult spinal deformity (ASD) is combined anterior-posterior staged surgery. When anterior surgery was first performed, oblique lumbar interbody fusion (OLIF) was employed; this method became increasing popular. This study aimed to determine the lordosis correction that can be achieved using OLIF and assess whether we can preoperatively predict the lordosis correction angle achieved using OLIF.Overview of Literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…They reported a significant difference in the age of patients who underwent MIS and those who underwent open surgeries, with older patients being more suited to MIS owing to poor bone quality and comorbidities. With aging patients who have degenerative scoliosis, MIS can correct sagittal and predominantly coronal deformities, with the LIF showing the greatest change [60][61][62].…”
Section: A B C D E Fmentioning
confidence: 99%
“…They reported a significant difference in the age of patients who underwent MIS and those who underwent open surgeries, with older patients being more suited to MIS owing to poor bone quality and comorbidities. With aging patients who have degenerative scoliosis, MIS can correct sagittal and predominantly coronal deformities, with the LIF showing the greatest change [60][61][62].…”
Section: A B C D E Fmentioning
confidence: 99%
“…In most studies on the role of OLIF in the correction of spinal deformities, the authors emphasize the need for posterior osteotomies to achieve an adequate degree of correction. Thus, Kim et al [ 60 ] found that although interbody fusion had some impact on balance correction, the main corrective effect could be achieved only after performing a dorsal approach using osteotomy of the articular processes or even a three-column osteotomy combined with transpedicular fixation. For the correction of rigid deformities, a three-stage treatment with OLIF has also been proposed: at the first stage, posterior release (osteotomy of the articular processes) is performed, at the second stage, multilevel OLIF, and at the third stage, final correction and transpedicular fixation [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The surgical oblique view during OLIF is much favorable for the surgeons as compared to LLIF, which only allows a vertical view. Similar to LLIF, OLIF can provide indirect neural decompression and deformity correction [ 29 , 56 , 83 , 84 ]. Meta-analyses have showed that the risks of ipsilateral hip flexor weakness, transient thigh pain, and lumbar plexus injury are lower in OLIF than in LLIF [ 77 , 85 , 86 ].…”
Section: Oblique Lumbar Interbody Fusionmentioning
confidence: 99%